Propuesta de un plan estratégico para el año 2016-2019 para la empresa Máxima Tecnología S.A. - Monge-Castro, Ricardo (Instituto Tecnológico de Costa Rica, 2015)
This work was performed in order to provide the Almacén Máxima Tecnología S.A an administrative tool to assist in their continuous improvement. The strategic plan contains the most relevant information necessary for the Company to do their jobs efficiently and effectively, because it shows the way forward to achieve a higher competitive level in our market, taking advantage of our resources and capabilities and our partners and strategic partners. This document presents a strategic analysis of the situation of the company, based on the strategic objectives which are formulated to achieve, and the strategies to achieve this, in addition to the action plans for its implementation are presented.
Proyecto de Graduación (Bachillerato en Administración de Empresas) Instituto Tecnológico de Costa Rica. Escuela Administración de Empresas, 2015.
Keywords: Mejoramiento continuo; Planeamiento estratégico; Análisis estratégico